Languages and ideologies at the Lower Yenisei (Siberia): Reconstructing past multilingualism. (August 2021) - Khanina, Olesya
Aims and objectives: This paper reconstructs past multilingualism (1900–1930s) among the nomadic people of the Lower Yenisei in northern Siberia, with particular attention to the language ideologies behind it; it is validated by parallels from small-scale communities worldwide. Approach: An ethnographic approach is taken, which interprets sociolinguistic data in view of emic categorizations. Data and analysis: The reconstruction is based on: (a) 1926 census data; (b) ethnographic reports from the 1920s to 1960s; (c) narratives from the 1940s; (d) retrospective sociolinguistic interviews; and (e) ethnonyms of local languages. (a), (b) provide a background for the interpretation of the linguistic data from (c)–(e). Findings: The connection of local social categories/groups to languages was unstable both synchronically and diachronically. Linguistic repertoires described the authenticity of the speech communities better than the command of individual languages. The linguistic indexing of identity was relational and depended on social networks more than on ancestry/kinship. These ideologies together with constant migrations shaped the sociolinguistic profile of the area and facilitated language shifts. Originality: Besides providing a detailed sociolinguistic description for an underresearched part of the world, this paper uses a novel methodology for reconstructing multilingualism of the past. Implications: The described mechanisms of language shift within communities that are multilingual in related languages contribute to theories of language diversification and spread at least in the north, but possibly also in a broader perspective. The methodology can be applied to other cases of past multilingualism.